Analysis of Ca2+ mediated signaling regulating Toxoplasma infectivity reveals complex relationships between key molecules. (9th January 2017) - Stewart, Rebecca J.; Whitehead, Lachlan; Nijagal, Brunda; Sleebs, Brad E.; Lessene, Guillaume; McConville, Malcolm J.; Rogers, Kelly L.; Tonkin, Christopher J.
Abstract: Host cell invasion, exit and parasite dissemination is critical to the pathogenesis of apicomplexan parasites such as Toxoplasma gondii and Plasmodium spp. These processes are regulated by intracellular Ca 2 + signaling although the temporal dynamics of Ca 2 + fluxes and down‐stream second messenger pathways are poorly understood. Here, we use a genetically encoded biosensor, GFP‐Calmodulin‐M13–6 (GCaMP6), to capture Ca 2 + flux in live Toxoplasma and investigate the role of Ca 2 + signaling in egress and motility. Our analysis determines how environmental cues and signal activation influence intracellular Ca 2 + flux, allowing placement of effector molecules within this pathway. Importantly, we have identified key interrelationships between cGMP and Ca 2 + signaling that are required for activation of egress and motility. Furthermore, we extend this analysis to show that the Ca 2 + Dependent Protein Kinases– Tg CDPK1 and Tg CDPK3—play a role in signal quenching before egress. This work highlights the interrelationships of second messenger pathways of Toxoplasma in space and time, which is likely required for pathogenesis of all apicomplexan species.